Metabolic Reprogramming and Reactive Oxygen Species in T Cell Immunity - Peng, Hao-Yun; Lucavs, Jason; Ballard, Darby; Das, Jugal Kishore; Kumar, Anil; Wang, Liqing; Ren, Yijie; Xiong, Xiaofang; Song, Jianxun (Frontiers in Immunology, 2021)
T cells undergo metabolic reprogramming and multiple biological processes to satisfy their energetic and biosynthetic demands throughout their lifespan. Several of these metabolic pathways result in the generation of reactive oxygen species (ROS). The imbalance between ROS generation and scavenging could result in severe damage to the cells and potential cell death, ultimately leading to T cell-related diseases. Interestingly, ROS play an essential role in T cell immunity. Here, we introduce the important connectivity between T cell lifespan and the metabolic reprogramming among distinct T cell subsets. We also discuss the generation and sources of ROS production within T cell immunity as well as highlight recent research concerning the effects of ROS on T cell activities.